Influence of Extrusion Process Conditions on the Residence Time and Throughput of a Twin-Screw Extruder Using Full Factorial Experimental Design - Yusuf, M.; Halilu, M.; Filli, K. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2021)
The effect of extrusion condition on residence time and throughput rate of a twin-screw extruder was investigated using blends of sorghum groundnut and tiger nut in twin-screw extruder SLG65 Model. In this study, a three factor 3-level full factorial experimental design was adopted. The influence of extrusion cooking conditions on both the combine effect and the effect of independent variables were evaluated. The analysis of variance showed that both linear and quadratic were not significant, however, interaction significantly (P<0.05) affect both the residence time and the throughput rate of the extruded. The results revealed that the throughput rate ranged from (0.012-0.040 Kg/s). The highest value was recorded at 100°C barrel temperature, 50:30:20 feed composition for ratios of sorghum groundnut and tiger nut and 18% feed moisture content. While the residence time ranged from (47 - 66.0 S) the highest residence time was obtained at 110°C barrel temperature 50:30:20 ratios of sorghum groundnut and tiger nut and 26 % feed moisture content. The information provided about the residence time and throughput rate of a twin-screw extruder will be used in fabricating an extruder that will be used in producing similar extruded product. The result of the research could be used by intended processors of similar extruded product to explore the possibility of producing similar product by manipulating the processing variables in order to obtain a desired product.